Transcriptomic Evidence Reveals the Molecular Basis for Functional Differentiation of Hemocytes in a Marine Invertebrate, Crassostrea gigas - Mao, Fan; Wong, Nai-Kei; Lin, Yue; Zhang, Xiangyu; Liu, Kunna; Huang, Minwei; Xu, Duo; Xiang, Zhiming; Li, Jun; Zhang, Yang; Yu, Ziniu (Frontiers in Immunology, 2020)
Hemocytes play unequivocally central roles in host immune defense of bivalve mollusks, though the exact mechanisms underlying their functional differentiation are only partially understood. To this end, granulocytes and hyalinocytes were sorted via flow cytometry from hemocytes of the Pacific oyster Crassostrea gigas, and consequently quantitative transcriptomic analysis revealed a striking array of deferentially expressed genes (DEGs), which were globally upregulated in granulocytes, dedicating to functional differentiation among oyster hemocytes. Our network of DEGs illustrated actively engaged signaling pathways, with Cdc42/Cdc42l being a core regulator of pathway network, which was validated by a dramatically reduced capacity for hemocytes phagocytosis in the presence of Cdc42 inhibitors. Additionally, a number of transcription factors were identified among DEGs, including ELK, HELT and Fos, which were predominantly expressed in granulocytes. The AP-1 transcription factor Fos was confirmed to facilitate functional differentiation of hemocytes in an assay on binding to target genes by the AP-1 binding site, consistent with downstream phagocytosis and ROS production. Importantly, Cdc42/Cdc42l were also regulated by the expression of Fos, providing a possible regulatory mechanism guided hemocyte functional differentiation. Findings in this study have bridged a knowledge gap on the mechanistic underpinnings of functional differentiation of hemocytes in a marine invertebrate C. gigas, which promise to facilitate research on the evolution of immune defense and functional differentiation of phagocyte in higher-order and more recent phyla.